Suicide-related behaviours in schizophrenia in China: a comprehensive meta-analysis. (25th September 2017) - Dong, M.; Wang, S. B.; Wang, F.; Zhang, L.; Ungvari, G. S.; Ng, C. H.; Meng, X.; Yuan, Z.; Wang, G.; Xiang, Y. T.
Abstract : Aims: Suicide-related behaviours are common in schizophrenia and are significantly associated with premature death. The objective of this meta-analysis study was to estimate the pooled prevalence of suicide-related behaviours in schizophrenia patients in China. Methods: The relevant literature was searched systematically via the relevant electronic databases (PubMed, Embase, PsycINFO, Chinese National Knowledge Infrastructure, Wanfang Databases and Chinese Biological Medical Literature Database) from their inception until 14 September 2016. Only original studies that reported the prevalence of suicide-related behaviours including suicidal ideation (SI), suicide plan, suicide attempt (SA) and completed suicide were selected. Results: Nineteen articles met the inclusion criteria and were analysed. The pooled lifetime prevalence of SI and SA were 25.8% (95% CI 14.7–41.1%) and 14.6% (95% CI 9.1–22.8%), respectively. The 1-month prevalence of SI was 22.0% (95% CI 18.2–26.4%). Subgroup analyses of lifetime SI and SA showed that gender, sample size, survey year, study location and source of patients have no significant mediating effects on the results. Conclusions: Suicide-related behaviours are common in Chinese schizophrenia patients. Due to the high mortality risk, regular screening and effective suicide prevention programmes are warranted.